1997
DOI: 10.1128/jb.179.19.6005-6009.1997
|View full text |Cite
|
Sign up to set email alerts
|

The bimodular G57-V577 polypeptide chain of the class B penicillin-binding protein 3 of Escherichia coli catalyzes peptide bond formation from thiolesters and does not catalyze glycan chain polymerization from the lipid II intermediate

Abstract: Because the specificity profile of the membrane anchor-free G57-V577 penicillin-binding protein 3 (PBP3) of Escherichia coli for a large series of ␤-lactam antibiotics is similar to that of the full-size membrane-bound PBP, the truncated PBP is expected to adopt the native folded conformation. The truncated PBP3 functions as a thiolesterase. In aqueous media and in the presence of millimolar concentrations of a properly structured amino compound, it catalyzes the aminolysis of the thiolester until completion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 30 publications
0
61
0
Order By: Relevance
“…Using ␤-lactams to probe the catalytic activity of PBP3 in growing cells makes it possible to assay the enzyme under conditions in which it is active in cell wall synthesis. These conditions cannot be replicated in vitro yet (1). We found that inhibition of cell division by a variety of methods had no detectable effect on the apparent rate of acylation of PBP3 with aztreonam or piperacillin but slightly reduced acylation with cephalexin.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Using ␤-lactams to probe the catalytic activity of PBP3 in growing cells makes it possible to assay the enzyme under conditions in which it is active in cell wall synthesis. These conditions cannot be replicated in vitro yet (1). We found that inhibition of cell division by a variety of methods had no detectable effect on the apparent rate of acylation of PBP3 with aztreonam or piperacillin but slightly reduced acylation with cephalexin.…”
Section: Discussionmentioning
confidence: 84%
“…Although PBP3 cannot be engaged in cell division under these conditions, it might still interact with some other division proteins. More recently, a truncated form of PBP3 that lacks its N-terminal membrane anchor sequence has been purified and shown to react with ␤-lactams at rates similar to those observed when native PBP3 is studied in isolated membranes (1). This finding argues against a requirement for allosteric activation, unless one supposes that the deletion itself activates the protein.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Interestingly, this peptide is a transmembrane helix (TMH). These findings help to clarify how targeting information is encoded in FtsI's primary sequence and demonstrate that a bacterial TMH can serve as a targeting signal.FtsI, also known as penicillin-binding protein 3 (PBP3), is a transpeptidase needed for cross-linking septal peptidoglycan (1,3,38). Previous studies from a number of laboratories have shown that FtsI is one of over a dozen proteins that localize to the division site, where they form a structure called the septal ring (for recent reviews, see references 12 and 43).…”
mentioning
confidence: 99%
“…The antibiotics chosen were the ß-lactams Aztreonam and Piperacillin. These compounds specifically inactivate PBP3 by acylating a serine of its transpeptidase catalytic site (Adam et al, 1997). For this analysis, MC4100 cells were grown in MS medium and at OD600nm=0.15, Aztreonam (0.25 µg/ml) was added to exponentially growing cells.…”
Section: Resultsmentioning
confidence: 99%